Meeting Abstracts of the 4th Uludag Cardiology Summit, March 7-10, 2024, Bursa, Türkiye - 4th Uludag Cardiology Summit (The European Research Journal, 2024)
OP-01. [Successful Lead Extraction and Repeat Pacemaker Implantation in a Patient with Paget-Schroetter Syndrome and Pacemaker Dysfunction] OP-02. Acute Coronary Syndrome in a Young Patient with Subsequent Psoriasis Diagnosis: A Case Report OP-03. Relationship between Triglyceride/High Density Lipoprotein Cholesterol Ratio and Functional Significance of Coronary Lesions OP-04. Biventricular Noncompaction with Ascending Aortic Dilatation Presenting with Congestive Heart Failure: A Rare Case of Nonischemic Cardiomyopathy OP-05. Evaluation of the Effect of Prognostic Nutritional Index on Mortality in Acute Heart Failure OP-06. Evaluation of Medication Use in Heart Failure Patients: An Observational Study OP-07. Evaluation of Increase in the Adhesion Molecules (ICAM-1, VCAM-1) According to the Types of Atrial Fibrillation OP-08. Wellens Syndrome Unveiled: A Case Report of Coronary Spasm in a 70-Year-Old Patient OP-09. [Chest Pain+Elevated Troponin Levels ≠ Acute Coronary Syndrome] OP-10. Radial Artery Spasm during Transradial Catheterization OP-11. The Effect of Naples Prognostic Score in Predicting Saphenous Vein Graft Disease in Patients with Coronary Bypass OP-12. Complete Atrioventricular Block due to Atrioventricular Node Invasion in a Malignant Melanoma OP-13. Effects of Upgrading from Right Ventricular Pacing to Cardiac Resynchronization Therapy and Comparison with Dual-Chamber Defibrillator in Patients with Heart Failure OP-14. [Chronic Inflammation Marker in Lower Extremity Peripheral Artery Patients: Platelet-Albumin Ratio] OP-15. Andersen-Tawil Syndrome Diagnosed with Bidirectional Ventricular Tachycardia during Pregnancy OP-16. Intercoronary Continuity between the Right and Left Anterior Descending Coronary Arteries Causing Acute Coranary Syndrome OP-17. Effect of Glyceryl Trinitrate-Containing or Lidocaine-Containing Cream Applications before Transradial Coronary Angiography on Procedure Success and Complications OP-18. [A Rare Complication after Transradial Intervention: Sterile Granuloma] OP-19. Multidisciplinary Management of a Common Variable Immunodeficiency Case with Myopericarditis OP-20. A Case with Coronary Perforation OP-21. [Experience with Percutaneous Catheter-Based Closure of Ventricular Septal Rupture Developing After Myocardial Infarction and Difficulties Encountered During The Procedure; Sharing Clinical Experience with 2 Cases] OP-22. Usability of Naples Prognostic Score Predicting Non-Dipper Pattern in Normotensive Patients OP-23. [The Intruder in The Right Ventricle: Cardiac Cyst Hydatic] OP-24. Challenging Rotablator Case Accompanied by IVUS OP-25. [ICD or No ICD? That is the Question!] OP-26. Electrical Storm of Malignant Ventricular Arrhythmia Confused with Epileptic Seizure OP-27. Allergy Related Acute Coronary Syndrome: Kounis Syndrome OP-28. Relationship between the Development of No-Reflow Phenomenon and Lymphocyte/HDL Ratio in Acute Coronary Syndrome Patients OP-29. [Once Upon a Time, Thrombus in the Right Atrium] OP-30. [From Diarrhea to the Heart! Tricuspid Valve Endocarditis] OP-31. [Delirium or Not?: Contrast Induced Encephalopathy] OP-32. Percutaneous Closure of an Iatrogenic Mitral Valve Perforation OP-33. Closure of a Paravalvular Leak between Ring and Valve: A Case Report OP-34. Effective Management of Cardiac Arrest with ST Elevation Myocardial Infarction and Severe Aortic Stenosis Patient: A Multidisciplinary Approach OP-35. [Carotid Stent Migration, a Rare Late Complication and Its Management] OP-36. Treatment of Total Ocluded RCA Because of Stent Detachment with Subintimal Crossing OP-37. A Case of Pericardial Effusion with Atypical Presentation OP-38. Percutaneous Treatment of Pseudoaneurysm with Graft Stent after Intervention of the Left Main Coronary Artery OP-39. A Rare Cause of Aortic Interruption: Mid Aortic Syndrome OP-40. Radial Artery Perforation and Its Treatment during Percutaneous Coronary Intervention OP-41. Transcatheter Closure of Atrial Septal Defect in Patients with Coronary Anomaly